Longitudinal wastewater surveillance of four key pathogens during an unprecedented large-scale COVID-19 outbreak in China facilitated a novel strategy for addressing public health priorities–A proof of concept study - Songzhe Fu; Yixiang Zhang; Rui Wang; Zhiqiang Deng; Fenglan He; Xiaotong Jiang; Lixin Shen (Water Research, 2023)

Westerly aridity in the western Tarim Basin driven by global cooling since the mid-Pleistocene transition - Hongye Liu; Rui Zhang; Yansheng Gu; Gaowen Dai; Lin Li; Shuo Guan; Zhongbiao Fu (Quaternary Science Reviews, 2023)

The roles of Methylobacterium organophilum and Sphingomonas melonis for accelerating N-methyl pyrrolidone (NMP) biodegradation - Yongyi Gao; Ting Chen; Yifan Hou; Ruiyun Xue; Rui Liu; Fu Chen; Yongming Zhang; Bruce E. Rittmann (Journal of Water Process Engineering, 2023)

Sources and solubility of aerosol phosphorus at a coastal site in northern China: Coarse versus fine particles and spring versus winter - Shuwei Dong; Huanhuan Zhang; Padmaja Krishnan; Shiguo Jia; Chengpeng Huang; Fu Wang; Lan Luo; Feng Wang; He Meng; Yujiao Zhu; Rui Li; Mingjin Tang (Atmospheric Environment, 2023)

The hepatoprotective effects of plant-based foods based on the “gut–liver axis”: a prospective review - Qiongdan Hu; Wan Liao; Zhen Zhang; Sanjun Shi; Shuguang Hou; Ningping Ji; Xinjie Zhang; Qian Zhang; Yangyang Liao; Linghui Li; Zongping Zhu; Yi Chen; et al. (Critical Reviews in Food Science and Nutrition, 2023)

GPCR signaling contributes to immune characteristics of microenvironment and process of EBV-induced lymphomagenesis - Jie Xiong; Yu-Ting Dai; Wen-Fang Wang; Hao Zhang; Chao-Fu Wang; Tong Yin; Shu Cheng; Hui-Juan Zhong; Shan-He Yu; Lu Jiang; Sheng-Yue Wang; Hai Fang; et al. (Science Bulletin, 2023)

Plant and animal positive-sense single-stranded RNA viruses encode small proteins important for viral infection in their negative-sense strand - Pan Gong; Qingtang Shen; Mingzhen Zhang; Rui Qiao; Jing Jiang; Lili Su; Siwen Zhao; Shuai Fu; Yu Ma; Linhao Ge; Yaqin Wang; Rosa Lozano-Durán; et al. (Molecular Plant, 2023)

A novel culture-enriched metagenomic sequencing strategy effectively guarantee the microbial safety of drinking water by uncovering the low abundance pathogens - Songzhe Fu; Yixiang Zhang; Rui Wang; Zhiguang Qiu; Weizhi Song; Qian Yang; Lixin Shen (Journal of Environmental Management, 2023)

Significantly improved high-temperature capacitive performance in polymer dielectrics utilizing ultra-small carbon quantum dots with Coulomb-blockade effect - Hangchuan Cai; Rui Wang; Bin Gou; Jing Fu; Yujie Zhu; Hao Yang; Jiangang Zhou; Manxi Li; An Zhong; Daoming Zhang; Huasong Xu; Chunhui Bi; et al. (Chemical Engineering Journal, 2023)

Meta-analytic and experimental evidence that warmer climate leads to shift from advanced to delayed spring phenology - Jing Guo; Qimei Ma; Hanfeng Xu; Yue Luo; Dashan He; Fucheng Wang; Jiasheng Wu; Yongshuo H. Fu; Jianquan Liu; Rui Zhang; Lei Chen (Agricultural and Forest Meteorology, 2023)

Quality assessment of the ionospheric density profiles based on long-term COSMIC 1 and 2 radio occultation observations - Na Fu; Rui Zhang; Qixin Pan; Xiaojing Tian; Shaoqiu Long; Chaolong Yao (Journal of Earth System Science, 2023)

Twice matched fruit counting system: An automatic fruit counting pipeline in modern apple orchard using mutual and secondary matches - Zhenchao Wu; Xiaoming Sun; Hanhui Jiang; Fangfang Gao; Rui Li; Longsheng Fu; Dong Zhang; Spyros Fountas (Biosystems Engineering, 2023)

Highly stable and selective Pt/TS-1 catalysts for the efficient nonoxidative dehydrogenation of propane - Weilong Hou; Kehang Lin; Xiangyu Zhang; Bowen Xu; Yuexia Wang; Xinqing Lu; Yijing Gao; Rui Ma; Yanghe Fu; Weidong Zhu (Chemical Engineering Journal, 2023)

From anaerobic digestion to single cell protein synthesis: A promising route beyond biogas utilization - Rui Li; XiaoLei Fan; YuFeng Jiang; RuoNan Wang; RongBo Guo; Yifeng Zhang; ShanFei Fu (Water Research, 2023)

Rare loss-of-function variants reveal threshold and multifactorial inheritance of dextrocardia - Zhongzhong Chen; Yunqian Gao; Lei Lu; Nan Li; Pei Liu; Rui Peng; Lingling Liu; Hefeng Huang; Qihua Fu; Haifa Hong; Jianguo Zhang; Hongyan Wang (Science Bulletin, 2023)

Unraveling the role of unpaired 3d electrons in e orbital of CoO: Driving π feedback of N2 for efficient ammonia electrosynthesis - Yuanyuan Xiong; Liang Zhao; Rui Zhao; Xiaoxuan Wang; Xinyue Chi; Kaixin Zhang; Zhenzhen Fu; Shuyuan Li; Jiaou Wang; Kaiqi Nie; Zhiyu Yang; Yi-Ming Yan (Chemical Engineering Journal, 2023)

Development and validation a prognostic model based on natural killer T cells marker genes for predicting prognosis and characterizing immune status in glioblastoma through integrated analysis of single-cell and bulk RNA sequencing - Jiahe Hu; Lei Xu; Wenchao Fu; Yanan Sun; Nan Wang; Jiheng Zhang; Chengyun Yang; Xiaoling Zhang; Yuxin Zhou; Rongfang Wang; Haoxin Zhang; Ruishu Mou; et al. (Functional & Integrative Genomics, 2023)

A new oleanane-type triterpene from Ardisia lindleyana D.Dietr and its cytotoxic activity - Zhou Tiqiang; Wei Zhenzhen; Fu Qianyu; Qiu Rui; Zhang Guangjie; Li Bin; Dong Junxing; Zeng Chengchu (Natural Product Research, 2023)

Graph neural network-based spatio-temporal indoor environment prediction and optimal control for central air-conditioning systems - Jing Zhang; Fu Xiao; Ao Li; Tianyou Ma; Kan Xu; Hanbei Zhang; Rui Yan; Xing Fang; Yuanyang Li; Dan Wang (Building and Environment, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Analysis of cuproptosis-related lncRNA signature for predicting prognosis and tumor immune microenvironment in pancreatic cancer - Hong-Fei Yao; Da-Peng Xu; Jia-Hao Zheng; Yu Xu; Qin-Yuan Jia; Yu-Heng Zhu; Jian Yang; Rui-Zhe He; Ding Ma; Min-Wei Yang; Xue-Liang Fu; De-Jun Liu; et al. (Apoptosis, 2023)

Magnetic anaerobic granular sludge for sequestration and immobilization of Pb - Rui Zhou; Han Li; Chengshuai Liu; Yizhang Liu; Jyh-Fu Lee; Yu-Jung Lin; Zhang Yan; Zhangyi Xu; Xiaoyun Yi; Chunhua Feng (Water Research, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

Phenotyping of individual apple tree in modern orchard with novel smartphone-based heterogeneous binocular vision and YOLOv5s - Guanao Zhao; Ruizhe Yang; Xudong Jing; Haosen Zhang; Zhenchao Wu; Xiaoming Sun; Hanhui Jiang; Rui Li; Xiaofeng Wei; Spyros Fountas; Huijun Zhang; Longsheng Fu (Computers and Electronics in Agriculture, 2023)

Highly synergistic and polarized KNbO3/WO3 heterojunction for piezo-photocatalytic degradation of organic pollutant - Rui Huang; Wei Cai; Heng Zhang; Zhenhua Wang; Qin Zhang; Rongli Gao; Gang Chen; Xiaoling Deng; Xiang Lei; Jiling Dong; Xiaoyan Liu; Chunlin Fu (Journal of Environmental Chemical Engineering, 2023)

Genome-Wide Identification and Expression Analysis of the CAD Gene Family in Walnut (Juglans regia L.) - Pengyu Wu; Rui Zhang; Shangqi Yu; Jiazhi Fu; Zhongzhong Guo; Dong Li; Zhiyong Pan; Haifang Hu (Biochemical Genetics, 2023)

Speed and temperature superposition on traffic speed deflectometer measurements - Miaomiao Zhang; Guozhi Fu; Yuetan Ma; Rui Xiao; Baoshan Huang (Transportation Geotechnics, 2023)

Manipulating electron redistribution of active sites by in situ engineering B-S-V bond in VS2 catalyst for stable nitrogen fixation - Xinyue Chi; Rui Zhao; Xiaoxuan Wang; Yuanyuan Xiong; Kaixin Zhang; Zhenzhen Fu; Yebo Yao; Shuyuan Li; Zhi-Yu Yang; Yi-Ming Yan (Chemical Engineering Journal, 2023)

Nitrogen addition mediates monospecific and mixed litter decomposition in a boreal peatland - Xiong-Fei Zhang; Nan-Hai Zhong; Rui Li; Fu-Xi Shi; Rong Mao (CATENA, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Canopy height, rather than neighborhood effects, shapes leaf herbivory in a tropical rainforest - Shuang Zhang; Guo‐Rui Xu; Yu‐Xin Zhang; Wen‐Fu Zhang; Min Cao (Ecology, 2023)
Factors shaping the interspecific variations in herbivory have puzzled ecologists for decades and several hypotheses have been proposed to explain interspecific variation in leaf herbivory. In a tropical rainforest in Yunnan Province, China, we collected 6732 leaves from 129 species with canopy heights ranging from 1.6 to 65.0 m above the ground. We tested the role of canopy height, the diversity, composition and structural heterogeneity of neighbors and leaf traits in shaping the interspecific variations in herbivory. Results show that leaf herbivory decreased with canopy height and specific leaf area (SLA) and increased with leaf size. However, neighboring species' diversity, composition, and structural heterogeneity showed no association with herbivory. Therefore, neither the visual apparency effect nor the associational resistance effect was detected in this hyperdiverse tropical rainforest. These findings highlight the importance of vertical structure in shaping herbivory patterns in natural communities.

Amorphous nanophosphates of dual-metal (Co and Ni) for the decomposition of ozone under humid conditions - Qian Zhang; Jifei Liao; Guangzhi Du; Yu Lin; Xiaoqiong Liu; Rui Wang; Lingyu Huang; Wenyan Xiao; Jiahao Chen; Yan Fu (Journal of Environmental Chemical Engineering, 2023)

GSK2795039 prevents RIP1-RIP3-MLKL-mediated cardiomyocyte necroptosis in doxorubicin-induced heart failure through inhibition of NADPH oxidase-derived oxidative stress - Xiao-Juan Zhang; Lu Li; Ai-Ling Wang; Hong-Xia Guo; Hui-Ping Zhao; Rui-Fang Chi; Hui-Yu Xu; Li-Guo Yang; Bao Li; Fu-Zhong Qin; Jia-Pu Wang (Toxicology and Applied Pharmacology, 2023)

A chitin synthase mutation confers widespread resistance to buprofezin, a chitin synthesis inhibitor, in the brown planthopper, Nilaparvata lugens - Bin Zeng; Fu-Rong Chen; Ya-Ting Liu; Di Guo; Yi-Jie Zhang; Ze-Rui Feng; Li-Xiang Wang; John Vontas; Shun-Fan Wu; Kun Yan Zhu; Cong-Fen Gao (Journal of Pest Science, 2023)

Abnormal fatty acid metabolism and ceramide expression may discriminate myocardial infarction from strangulation death: A pilot study - Song-Jun Wang; Bing-Rui Liu; Fu Zhang; Ya-Ping Li; Xiao-Rui Su; Chen-Teng Yang; Bin Cong; Zhi-Hua Zhang (Tissue and Cell, 2023)

Facilitating both anionic and cationic redox processes in Na-rich layered cathode materials by heteroatomic doping - Ziwei Chen; Maolin Yang; Zhongyuan Huang; Yanda Fu; Zhefeng Chen; Simo Li; Minzhi zhan; Rui Wang; Mihai Chu; Rui Qi; Xing Cheng; Zhewen Ma; et al. (Chemical Engineering Journal, 2023)

An interfacial gas-enrichment strategy for mitigating hydrate adhesion and blockage - Rui Ma; Senbo Xiao; Yuanhao Chang; Yuequn Fu; Jianying He; Zhiliang Zhang (Chemical Engineering Journal, 2023)

Phosphorus availability mediates plant–plant interaction and field productivity in maize-grass pea intercropping system: Field experiment and its global validation - Shuang-Guo Zhu; Hong-Yan Tao; Wen-Bo Li; Rui Zhou; Yan-Wen Gui; Li Zhu; Xiao-Lin Zhang; Wei Wang; Bao-Zhong Wang; Fu-Jian Mei; Hao Zhu; You-Cai Xiong (Agricultural Systems, 2023)

Unique bacterial communities and lifestyles in deep ocean blue holes: Insights from the Yongle Blue Hole (South China Sea) - Shun Zhou; Jiwen Liu; Peng Yao; Liang Fu; Zuosheng Yang; Yulin Zhang; Rui Du; Chao Jia; Lin Chen; Jinchang Liang; Xiaolei Wang; Xiaochong Shi; et al. (Frontiers in Marine Science, 2023)
Deep ocean blue holes possess steep physicochemical gradients, especially low dissolved oxygen concentration, which shape the extraordinary microbial communities. However, the environmental responses of microorganisms with different lifestyles and knowledge of culturable microorganisms in the blue holes are still unknown. Here, we investigated the bacterial community structure with different lifestyles of the world’s deepest blue hole - the Yongle Blue Hole (YBH) in the South China Sea using both culture-dependent and -independent methods. YBH can be divided by oxygen content into an oxic zone, a suboxic zone and two anoxic zones. The abundance of bacteria, archaea, genes dsrB and soxB were all higher in the free-living (FL) lifestyle than in the particle-associated (PA) lifestyle, yet the diversity and richness of PA bacteria were higher than that of FL bacteria. More Gammaproteobacteria and less Alphaproteobacteria , Chloroflexi and Nitrospinae were observed within the FL fraction than within the PA fraction. The relative abundance of sulfur-oxidizing bacteria (SOB) was dominant between 100-140 m (anoxic zone I) in YBH, with a maximum of 90.0% (140 m FL fraction). The SOB in YBH were mainly colorless sulfur bacteria and purple non-sulfur bacteria, of which Thiomicrorhabdus and Sulfurimonas were the main representatives. In addition, a total of 294 bacterial strains were isolated on a variety of media and culture conditions, and 22.2% (18/81) of anaerobic strains were identified as potential novel species. Our study reveals a distinction between FL and PA bacteria in YBH. It contributes to further understanding of the bacterial community in deep ocean blue holes, and provides bacterial resources for subsequent studies on their adaptation to extreme marine environments.

RNA-seq for comparative transcript profiling in leaves of strawberry seedlings under salinity stress - Rui Zhang; Qiuli Du; Wenzhe Zhao; Long Yang; Dongmei Li; Xiude Chen; Wei Xiao; Xiling Fu; Chao Yang; Ling Li (Plant Biotechnology Reports, 2023)

Wastewater treatment by anodic oxidation in electrochemical advanced oxidation process: Advance in mechanism, direct and indirect oxidation detection methods - Rui Fu; Peng-Shuang Zhang; Yuan-Xing Jiang; Lin Sun; Xu-Hui Sun (Chemosphere, 2023)

Learn then match: A fast coarse-to-fine depth image-based indoor localization framework for dark environments via deep learning and keypoint-based geometry alignment - Qing Li; Rui Cao; Jiasong Zhu; Hao Fu; Baoding Zhou; Xu Fang; Sen Jia; Shenman Zhang; Kanglin Liu; Qingquan Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Four-armed host-defense peptidomimetics-augmented vanadium carbide MXene-based microneedle array for efficient photo-excited bacteria-killing - Xiaoqian Feng; Dongyi Xian; Jintao Fu; Rui Luo; Wenhao Wang; Yuwei Zheng; Qing He; Zhan Ouyang; Shaobin Fang; Wancong Zhang; Daojun Liu; Shijie Tang; et al. (Chemical Engineering Journal, 2023)

Shape-controlled synthesis of Pd nanotetrahedrons with Pt-doped surfaces for highly efficient electrocatalytic oxygen reduction and formic acid oxidation - Liuxuan Luo; Zehao Tan; Cehuang Fu; Rui Xue; Xiaojing Cheng; Tianzi Bi; Lutian Zhao; Yangge Guo; Xiyang Cai; Jiewei Yin; Shuiyun Shen; Junliang Zhang (Chemical Engineering Journal, 2023)

Selection and modification of ground motion records using Newmark-Hall spectrum as target spectrum for long-period structures - Jianyu Fu; Dongsheng Wang; Rui Zhang; Xiaoyu Chen (Earthquake Engineering and Engineering Vibration, 2023)

Evaluating the effects of contact time and leaching solution on measured solubilities of aerosol trace metals - Rui Li; Shuwei Dong; Chengpeng Huang; Feng Yu; Fu Wang; Xiaofei Li; Huanhuan Zhang; Yan Ren; Mingxian Guo; Qingcai Chen; Baozhu Ge; Mingjin Tang (Applied Geochemistry, 2023)